Anatomic Two-dimensional and Three-dimensional Models for Cyclic Fatigue Testing of Endodontic Instruments - Piasecki, Lucila; Makowka, Steven Robert; Gambarini, Gianluca (Iranian Endodontic Journal, 2020)
Introduction: In this study, new devices were developed and evaluated for cyclic fatigue testing (CTF) of endodontic instruments in two-dimensional (2D) and three-dimensional (3D) replicas of the internal anatomy of a mesial root of a mandibular molar. Methods and Materials: The trajectories of both curved mesial canals of the same root were outlined from computed tomographic scans and exported to a computer assisted drawing (CAD) software. In the CAD program, the canals were virtually enlarged to a size 25/0.06. The CTF devices were then prototyped in stainless steel. The 2D models represented the bucco-lingual (BL) and mesio-distal (MD) views of the canals, while the original trajectory was kept in the 3D model. Vortex Blue 25/0.06 instruments were tested for fatigue in the six canals (n=12). The number of cycles to failure (NCF) and fragment length (mm) were recorded. Data was statistically analyzed (ANOVA and post-hoc Games-Howell test) with the level of significance set at 5%. Results: The mean NCF was significantly different among all the canals (P<0.05). The lifespan of the files was greater in the 2D-BL models, followed by the 2D-MD and 3D. The mean fragment length was also different among the tested models (P<0.05). Conclusions: The tested 2D and 3D representations of the same canal trajectory resulted in significant differences both in the amount of stress (seen from NCF) and localization of the maximum stress (seen from fragment length). Further investigations are required to better understand the effects of different 3D curvatures on the cyclic fatigue of endodontic instruments. Keywords: Cyclic Fatigue; Dental Instruments; Endodontics; Nickel-Titanium